Upper limb rehabilitation with virtual environments: a review - Guzman, D. E.; Londoño, J. (Revista Mexicana de Ingenieria Biomedica, 2016)
This article gives the results of a literature review process about upper limb rehabilitation based on virtual environments. The study borns of the following questions about the current state of knowledge in this subject: how virtual environments influence traditional rehabilitation?, Which performance metrics have been applied to upper limb virtual rehabilitation? and which hardware devices are used in virtual rehabilitation? To answer the above questions a search for scientific articles was made in the search engine Google Scholar and databases PubMed, HINARI, ProQuest and Science Direct. The conducted review concluded that despite the existence of dozens of performance indicators to quantify the driving ability, there are no criteria to select a better index that best suits the objectives of a rehabilitation process.